Theme Based Instruction Model in Teaching Extensive Reading - Mutiarani Mutiarani; Irpan Ali Rahman (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2019)
The purpose of this study is to investigate in detail the implementation of theme based instruction model in teaching extensive reading. This study is classroom action research conducted at the fourth semester students’ English Educational Sciences, Educational Sciences Faculty, Universitas Muhammadiyah Jakarta with participant number are 40 students. Data obtained from the result of the test in each cycle. The findings showed that the learning process using theme based instruction model in teaching extensive reading makes the students more participative and active in their classroom reading learning process, it is showed by their high participation during the teaching is increased. Another finding revealed that there is significant influence toward the students’ extensive reading learning process from preliminary to cycle II stage in the research process. The average score of students at the preliminary stage is only 68 then it increased to 72 in the first cycle and increased significantly in cycle II with the amount of 83. It can be concluded that classroom action research is done by using of theme based instruction model in teaching extensive reading in the fourthsemester students of English Educational Sciences significantly helps the students in increasing about 21% improvement from pre-cycle to cycle II in their Extensive Reading course. This study recommends the continuation of using various teaching models for university students to improve their English language skills, especially English reading skill.